KETERAMPILAN MENULIS PARAGRAF EKSPOSISI SISWA KELAS X SMA NEGERI 12 PADANG DENGAN MENGGUNAKAN METODE DEMONSTRASI - Jarnah, Adek - (Pendidikan Bahasa Indonesia, 2014)
This study aimed to describe the skills of writing a paragraph of exposition tenth grade students of SMA Negeri 12 Padang using demonstration method. This type of research is classified as quantitative research using descriptive method. The population in this study were students of class X SMA Negeri 12 Padang terdatar the 2013/2014 school year, as many as 210 people were scattered in the 7th grade. The sampling technique used is proportional random sampling. Based on the results of the study concluded the following. First, write a paragraph of exposition skills class X SMA Negeri 12 Padang using demonstration method for indicator 1 (in the form of writing that gives relatively good understanding and knowledge (76-85%). Secondly, paragraph writing skills exposition tenth grade students of SMA Negeri 12 Padang by using the method of demonstration for indicator 2 (answering the question of what, why, when, and how) classified more than enough (66-75%). Thirdly, exposition paragraph writing skills by using the demonstration method for indicator 3 (delivered with straightforward language and language raw) classified more than enough (66-75%). Fourth, exposition paragraph writing skills by using the demonstration method for indicator 4 (using neutral tones, impartial and impose the will of the writer to the reader) are classified as good (76-85%).